Interferensi Gramatikal dalam Percakapan Mahasiswa Pemelajar Bahasa Jepang Tingkat Shochuukyuu - Anisa Arianingsih (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2022)
Abstract This study aims to determine the form of grammatical interference in Japanese conversation at pre-intermediate level students. The research method used the note-taking technique. The data is in the form of recorded conversations of 42 students of the 3rd semester Japanese Department of Unikom in 2022/2023 academic year who contracted the Shochuukyuu Kaiwa I course. The results showed that of the 70 interferences found, the most grammatical interference was found in changes in the form of the verb (40%), followed by the use of particles (28.6%), changes in adjective form (15%), and forms of explanation and explained (DM and MD) by 10%, while interference in the SKOP structure pattern was not found. This is because students at the pre-intermediate level have mastered basic Japanese sentence patterns that place the predicate at the end of the sentence. Keywords: Conversation, grammatical interference, pre-intermediate Abstrak Penelitian ini bertujuan untuk mengetahui bentuk interferensi morfologi dalam percakapan bahasa Jepang pada mahasiswa tingkat shochuukyuu. Metode penelitian menggunakan teknik simak catat. Data berupa rekaman hasil percakapan 42 mahasiswa semester III Program Studi Sastra Jepang Unikom tahun akademik 2022/2023 yang mengontrak mata kuliah Shochuukyuu Kaiwa I. Hasil penelitian menunjukkan bahwa dari 70 interferensi yang ditemukan, interferensi gramatikal paling banyak ditemukan pada perubahan bentuk kata kerja (40%), diikuti oleh penggunaan partikel (28,6%), perubahan bentuk kata sifat (15%), dan bentuk kata penerang dan diterangkan (DM dan MD) sebanyak 10%, sedangkan interferensi dalam pola struktur SKOP tidak ditemukan. Hal ini dikarenakan mahasiswa tingkat Shochuukyuu sudah menguasai pola kalimat dasar bahasa Jepang yang menempatkan predikat pada akhir kalimat. Kata kunci: Interferensi gramatikal, percakapan, shochuukyuu